2019
DOI: 10.1080/15384047.2019.1647058
|View full text |Cite
|
Sign up to set email alerts
|

LINC01133 promotes the progression of cervical cancer by sponging miR-4784 to up-regulate AHDC1

Abstract: Cervical cancer, as the deadliest gynecological tumor with high risk of incidence, manifests aberrantly expressed lncRNAs in the malignant cellular processes. Long intergenic non-protein coding RNA 1133 (LINC01133) has been acknowledged to actively participate in aggressive tumor phenotypes. Our study focused on the identification of the function and corresponding mechanism of the novel molecule, LINC01133 in cervical cancer. LINC01133 expression profile was validated by digging The Cancer Genome Atlas (TCGA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…There is accumulating evidence that the downstream targets and signaling pathways regulated by LINC01133 contributes to the malignant behavior of multiple types of cancer cells. [29][30][31][32] In nonsmall cell lung carcinoma, LINC01133 suppresses the transcription of KLF2, P21, and E-cadherin by binding to EZH2 and LSD1, resulting in increased cancer cell growth and invasion. 33 In colon cancer, LINC01133 inhibits EMT and metastasis by interacting with SRSF6.…”
Section: Discussionmentioning
confidence: 99%
“…There is accumulating evidence that the downstream targets and signaling pathways regulated by LINC01133 contributes to the malignant behavior of multiple types of cancer cells. [29][30][31][32] In nonsmall cell lung carcinoma, LINC01133 suppresses the transcription of KLF2, P21, and E-cadherin by binding to EZH2 and LSD1, resulting in increased cancer cell growth and invasion. 33 In colon cancer, LINC01133 inhibits EMT and metastasis by interacting with SRSF6.…”
Section: Discussionmentioning
confidence: 99%
“…in non-small-cell lung cancer [26,27], colorectal cancer [28] and osteosarcoma [29]. It could promote NSCLS cells' proliferation, migration and invasion through binding to EZH2 and LSD1 to repress KLF2, P21 and E-cadherin transcription [27].…”
Section: Discussionmentioning
confidence: 99%
“…There is accumulating evidence that the downstream targets and signaling pathways regulated by LINC01133 are involved in the malignant behavior of multiple types of cancer cells [26][27][28][29]. In non-small cell lung carcinoma, LINC01133 suppresses the transcription of KLF2, P21 and E-cadherin by binding to EZH2 and LSD1, resulting in increased cell growth and invasion [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LINC01133, a novel lncRNA, was first reported in 2015 to be highly expressed in lung squamous cell carcinoma (LSCC), but not in lung adenocarcinoma [ 27 ]. Recently, it has been verified that LINC01133 is involved in multiple types of malignant tumors, such as LSCC, osteosarcoma [ 20 ], cervical cancer [ 28 ], hepatocellular carcinoma [ 29 ], colorectal cancer (CRC) [ 30 ], and gastric carcinoma [ 31 ]. These studies collectively suggested that LINC01133 is an important regulator of cell proliferation and tumorigenesis, and may be a potential therapeutic target.…”
Section: Introductionmentioning
confidence: 99%